The Relationship between Learning Style and Listening Comprehension Achievement of Twelfth Grade Students of SMA Pusri Palembang - eska putri afriani (Edukasi, 2017)
This research aimed to describe the relationship between students’ learning style and their achievement in listening skill. The method which was used in this research was correlational research. The population of the research was the twelfth grade students of SMA Pusri Palembang in the 2016/2017 academic year. There are 128 students from five classes as the population in this research. The sample was taken by using convenience sampling which consist of 86 students. Furthermore there were two variables in this research. The first one was students’ learning style (variable X) and the second one was students’ achievement in listening skill (variable Y). The students’ learning style score was taken from the questionnaire whereas the student’ achievement in listening was taken from scoring. Based on the data analysis, it was found that the r-obtained (-.084) was lower than r-table (0.1765). then the level of probability (p) significance (sig.2-tailed) was .443. It means that p (.443) was higher than .05. It means that null hypothesis (H0) is accepted and the alternative hypothesis (Ha) is rejected. From the research finding, it can be concluded that there was no significant relationship between students’ learning style and their achievement in listening skill. It means that students’ learning style is not a dominant factor that affects listening achievement.